Examining the relationship between COVID-19 vaccines and recall rates in breast screening - Squillace, Lorena; Pizzi, Lorenzo; Chierghin, Angela; Bazzani, Carmen; Saguatti, Gianni; Tafà, Alfredo; Roti, Lorenzo; Mezzetti, Francesco (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. It has been observed that women vaccinated against coronavirus disease 2019 (COVID-19) may show axillary lymphadenopathy at screening mammogram, which may become suspicious for malignancy, leading to an increased recall rate for further diagnostic evaluations and a higher number of false-positive results, as well as considerable emotional distress for the women involved. Study design. The study aimed to assess the incidence of doubt/positive results in the 1st level mammogram among women who received a COVID-19 vaccine within 4 weeks before mammogram, compared to unvaccinated women. Further aims included the analysis of the distribution of doubt/positive 1st level screening mammogram results according to different women-related and diagnostic work-up-related characteristics, and the evaluation of the incidence of false-positive results observed at the 2nd level. Methods. The cohort study was carried out by retrospectively reviewing electronic data records related to the breast screening program of the Local Health Authority of Bologna in 2021 concerning women between 45 and 74 years old. Excluded were the women outside the age range, with prior breast cancer history, or receiving COVID-19 vaccination more than 4 weeks before the mammogram. Results. A total of 43,856 (mean age 56.6 ± 8.7) women met the study’s inclusion criteria. Among all enrolled women, the recall rate was 5.5% (N=2,394). There were no statistically significant differences in doubt/positive results between vaccinated within 4 weeks before the mammogram and unvaccinated women (5.5% versus 5.4%, p=0.649). However, those who received the Pfizer vaccine showed a significantly higher rate of doubt/positive results. Conclusions. Healthcare professionals’ awareness of vaccine records and educating patients about rare adverse effects can help prevent unnecessary biopsies, interventions, and changes in patient management. Further research is needed to confirm our findings